The British Army of the Rhine : turning Nazi enemies into Cold War partners - Speiser, Peter, 1975- (History of military occupation., 2016)
Between 1945 and 1957, West Germany made a dizzying pivot from Nazi bastion to Britain's Cold War ally against the Soviet Union. Successive London governments, though often faced with bitter public and military opposition, tasked the British Army of the Rhine (BAOR) to serve as a protecting force while strengthening West German integration into the Western defense structure. This book charts the BAOR's fraught transformation from occupier to ally by looking at the charged nexus where British troops and their families interacted with Germany's civilian population. Examining the relationship on many levels, the book ranges from how British mass media representations of Germany influenced BAOR troops to initiatives taken by the Army to improve relations. It also weighs German perceptions, surveying clashes between soldiers and civilians and comparing the popularity of the British services with that of the other occupying powers. As the book shows, the BAOR's presence did not improve the relationship between British servicemen and the German populace, but it did prevent further deterioration during a crucial and dangerous period of the early Cold War. An incisive look at an under-researched episode, this book sheds new light on Anglo-German diplomatic, political, and social relations after 1945, and evaluates their impact on the wider context of European integration in the postwar era.--